The Influence of Budget Participation, Accountability, Transparency and Organizational Culture As Moderating Variable on Financial Performance - Astuti Ekawati; Sri Isnowati (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of the study was to test and analyze the effect of budget participation, accountability and transparency on the financial performance of BPSDMD Central Java Province. To test and analyze the organizational culture moderates the influence of budget participation, accountability and transparency on the financial performance of BPSDMD Central Java Province. The population in this study were employees at the Regional Human Resources Development Agency of Central Java Province, totaling 200 people. The sample in this study were employees of the Regional Human Resources Development Agency of Central Java Province. Sampling with purposive sampling technique. Determination of the number of samples using the Slovin formula obtained a sample of 133 respondents. The data collection method used a questionnaire. Data analysis using linear regression analysis. Based on the results of the study, it can be concluded that budget participation, accountability and transparency have a positive and significant effect on financial performance at the Regional Human Resources Development Agency of Central Java Province. Organizational culture does not moderate the effect of budget participation and transparency on financial performance at the Regional Human Resources Development Agency of Central Java Province. Organizational culture moderates the effect of accountability on financial performance at the Regional Human Resources Development Agency of Central Java Province.